UMP STEM bot as educational kit for robotics and computer programming - Nurul Hazlina, Noordin; Hao, Mok Ren; Ikhwan Hafiz, Muhamad
We present UMP STEM Bot, an open-source robotic platform, for educational use that covers a wide spectrum of black-box and white-box learning objectives. The building structure of UMP STEM Bot and its learning outcomes are described. The educational kit is scalable to a more advance application as it is built based on the open-source technology. The UMP STEM Bot is a viable low-cost robotic manipulator platform alternative for introductory courses such as basics of robotics, computational thinking, and programming, as well as for advance courses at the university level such as intelligent robotics.